Modeling moisture redistribution of drip irrigation systems by soil and system parameters: regression-based approaches - Karimi, Bakhtiar; Karimi, Nazir; Shiri, Jalal; Sanikhani, Hadi (Stochastic environmental research and risk assessment, 2022)
One of the strategies for increasing water use efficiency and reducing deep percolation of drip irrigation systems is considering the patterns of moisture redistribution after cut-offing the irrigation process. Accurate estimation of the wetting dimensions in surface/subsurface irrigation systems is very important for optimal management of drip irrigation systems as well as minimizing water losses via deep percolation and runoff. An experimental study was conducted in the present research to evaluate the moisture redistribution process under surface and subsurface pulse drip irrigation systems and developing new regression-based methodologies for estimating moisture redistribution dimensions using both the soil and system parameters. A physical model was made and the experiments were performed on three different types of soil texture (fine, medium, and coarse) with three emitter flow rates (2, 4, and 6 lit/hr) in three emitter installation depths (0, 15, and 30 cm). The experiments were conducted for both continuous (CI) and pulse (PI) irrigation modes. The results showed that significant amounts of wetting dimensions and wetted area of the moisture bulb are related to the post-cut-offing stage. Then, using the nonlinear regression analysis, several models were proposed to estimate the horizontal and vertical redistribution pattern as well as the wetted area (upper and lower parts of the emitter). The comparison of the measured and the simulated values indicated that the non-linear regression models simulated the parameters associated with the redistribution, accurately. For instance, the MAE , RMSE , and NS values corresponding to the simulation of the horizontal redistribution vary between 0.19–0.72, 0.25–0.83 cm, and 0.77–0.96, respectively. These values for vertical downward redistribution vary between 0.13–0.59, 0.17–0.79 cm and 0.65–0.98 for all investigated treatments, respectively. The use of these models for design goals facilitates the determination of the accurate distance between laterals and emitters as well as the suitable depth of emitters.